PENGARUH EARNING PER SHARE (EPS), UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Saham Syariah Makanan & Minuman Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2019-2021) - M. taufik ridho; Thiyas fitri ayu adheansyah; Intan fazira; Deni yulia citra; Amelia safitri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study discusses company value and financial ratios based on the financial statements of companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The purpose of this study was to determine whether Earning Per Share (EPS), Firm Size, Profitability and Leverage have an influence on firm value.This study was built with five hypotheses, namely (1) Earning Per Share (EPS) has a negative effect on firm value. (2) Firm size has a negative effect on firm value. (3) Profitability has a positive effect on firm value. (4) Leverage has a positive effect on firm value.The type of data in this study is secondary data. The sample in this study used purposive sampling and polling methods. The sample companies are 11 sharia stock companies listed in food & beverage companies listed on the Indonesia Stock Exchange during the 2019-2021 period. This research is quantitative, and statistical testing uses multiple linear regression.By using regression analysis, it can be seen that the variables Earning Per Share (EPS), Firm Size, Profitability and Leverage simultaneously have a significant effect on firm value. The results of Partial Test, Leverage and Profitability have a positive and significant effect on firm value. Earning Per Share (EPS) and Firm Size have a negative and significant effect on firm value.